Pemilihan Layanan Satuan Pendidikan SMP oleh Pelajar yang Berdomisili di Kecamatan Kuranji Kota Padang - Fazil Akbar; Yurni Suasti; Triyatno . (JURNAL BUANA, 2018)
Aims of this research was to describe how junior high school of education unit service selected by students who are domiciled in Subdistrict Kuranji and reasons of students in choosing the education level of junior high school. This research is descriptive research with quantitative approach. The population of this research is the junior high school students residing in Kuranji district by the 8094 people. Withdrawal of samples using a proportional random sampling with a total of 98 people. Data were collected through interviews using questionnaires, then a descriptive analysis techniques and using percentage. This research found that service units selected by the Junior High School education students at Kuranji Subdistrict tend to be balanced between the select service in the districts and are outside the district, namely, 52 percent chose education service located in Sub Kuranji, while 48 percent chose education service outside the Sub Kuranji. The reasons students choose a JUNIOR HIGH SCHOOL in the district, the vast majority choose because it's close to home. For students choosing junior high school lies outside the district, most of the memlih due to the popularity and the school's accreditation, and encouragement of parents.